2006
DOI: 10.1021/jp062456u
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Analyzed Threshold Ionization Study of Vinyl Chloride Cation in the First Excited Electronic State Using Vacuum Ultraviolet Radiation in the 107−102.8 nm Range

Abstract: Vibrational spectrum of vinyl chloride cation in the first excited electronic state, A2 A', was obtained by one-photon mass-analyzed threshold ionization (MATI) spectroscopy. Use of an improved vacuum ultraviolet radiation source based on four-wave sum frequency mixing in Hg resulted in excellent sensitivity for the MATI signals. From the MATI spectrum, the ionization energy to the A2 A' state of the cation was determined to be 11.6667 +/- 0.0006 eV. Nearly complete vibrational assignment for the MATI peaks wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…Using the reported experimental AIE values for value for the 1 2 A′ state is evaluated to be 1.72 eV. The experimental geometry of the A state of C 2 H 3 Cl + was reported by Kim et al, 4 and we found no reported experimental geometries for the other three states in the literature. Photodissociation studies for the C 2 H 3 Cl + ion were carried out by several groups, 5,[11][12][13]17,18 and the observed products and the measured dissociation energies and appearance energies were reported.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Using the reported experimental AIE values for value for the 1 2 A′ state is evaluated to be 1.72 eV. The experimental geometry of the A state of C 2 H 3 Cl + was reported by Kim et al, 4 and we found no reported experimental geometries for the other three states in the literature. Photodissociation studies for the C 2 H 3 Cl + ion were carried out by several groups, 5,[11][12][13]17,18 and the observed products and the measured dissociation energies and appearance energies were reported.…”
Section: Introductionmentioning
confidence: 72%
“…Experimental vertical ionization energies (VIEs) for the four states of C 2 H 3 Cl + were already reported by many groups. [3][4][6][7][8][9][10][11][12][13][14][15][16] On the basis of the experimental VIE values for different states of the ion, relative energy values (denoted by T v ′ in the present paper) of the excited states to the ground state of the ion at the ground-state geometry of the neutral molecule can be evaluated. Using the experimental VIE values for the X, A, B, and C states (10.18, 11.72, 13.14, and 13.56 eV, respectively) reported by Lake and Thompson, 6 the T v ′ values for the 1 2 A′, 2 2 A′′, and 2 2 A′ states are evaluated to be 1.54, 2.96, and 3.38 eV, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Although multiphoton excitation by pulsed lasers via an intermediate excited state is currently the most typical method to generate molecules in Rydberg states, one-photon ionization with vacuum ultraviolet (VUV) radiation is advantageous as the intensities of vibronic bands can be compared with Franck−Condon factors (FCFs) between the neutral ground state and the ionized state . Recently Kim et al developed VUV radiation sources of up to 12 eV by four-wave mixing of Hg, which was successfully applied to generate not only the ground but also the first excited ionized state of vinyl halides. , Vibronic bands in MATI spectra of the ground and first excited states of radical cations were successfully analyzed using calculated FCFs.…”
Section: Introductionmentioning
confidence: 99%
“…A series of sharp peaks is observed in the energy range of 11.6−12.1 eV, which are assigned to the vibrational bands of the A 2 A′ state based on previously reported conclusions. 9,11 The peak with a maximum intensity at 11.670 eV is assigned to the origin band of the A 2 A′ state. The v 6 (C−H−H rock), v 8 (C−Cl stretching), and v 9 (C−C−Cl bend) vibrational modes are also populated.…”
Section: Cl-loss Potential Energymentioning
confidence: 99%
“…The adiabatic ionization energy of C 2 H 3 Cl was determined to be 10.0062 ± 0.0003 eV using high-resolution zero-kinetic-energy (ZEKE) PES . The ionization energy of the A 2 A′ and B 2 A″ states was measured using mass-analyzed threshold ionization (MATI) and MATI photodissociation yield (PDY) spectroscopy . In the MATI-PDY spectrum, several vibrational peaks were observed in the lower-energy region of the B 2 A″ state, implying that the ionic state has a shallow potential well …”
Section: Introductionmentioning
confidence: 99%